2014
DOI: 10.1097/brs.0000000000000408
|View full text |Cite
|
Sign up to set email alerts
|

The Cascade of Medical Services and Associated Longitudinal Costs Due to Nonadherent Magnetic Resonance Imaging for Low Back Pain

Abstract: Supplemental Digital Content is Available in the Text.Magnetic resonance imaging (MRI) without clear indications led to a cascade of subsequent diagnostic and invasive services, which occurred within 6 months after imaging. Early MRI was significantly associated with a large and sustained escalation in medical costs, even after grouping by severity and controlling for pain and demographic covariates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 37 publications
0
47
0
1
Order By: Relevance
“…The database has complete capture of individual medical and indemnity services provided to injured workers, and has been used for a number of national health services research studies 21, 22, 23. The distribution of occupational injuries/disorders and overall medical costs is comparable to national occupational injury datasets, such as the Bureau of Labor Statistics (BLS) and the National Council on Compensation Insurance 24.…”
Section: Methodsmentioning
confidence: 99%
“…The database has complete capture of individual medical and indemnity services provided to injured workers, and has been used for a number of national health services research studies 21, 22, 23. The distribution of occupational injuries/disorders and overall medical costs is comparable to national occupational injury datasets, such as the Bureau of Labor Statistics (BLS) and the National Council on Compensation Insurance 24.…”
Section: Methodsmentioning
confidence: 99%
“…the disclosure of irrelevant changes in the structure of the intervertebral discs, vertebral bodies and processes, which also occur in people with no symptoms, causes adverse effects in patients. this confirms in them a sense of disease, increases the sensation of pain, and causes more frequent reporting on the visit and more aggressive, risky and complicated treatment [13,14]. of course, the expansion of diagnosis is required when there is no improvement after several weeks of treatment, or new symptoms appear which suggest a specific cause of pain.…”
Section: Low Back Pain In the Course Of Other Diseasesmentioning
confidence: 86%
“…Diagnostic errors can, and do, occur in response to extraneous contextual information. For example, pathologists can be influenced in their subjective interpretation of pap smears based on the availability of objective DNA results , radiologists in their interpretation of MRI images , and clinicians in their treatments . At this point , the benefit of blinding procedures to clinical decision‐making is still an open question : One main reason is that an initial clinical diagnosis is normally made by one responsible stakeholder, often under time pressure.…”
Section: Recent Approaches 2000–2016mentioning
confidence: 99%
“…Examples of such errors within the forensic sciences include fingerprint identification errors (10), DNA mixture judgments (11), and FBI hair analysis (12). Within the clinical diagnostic realm, research has shown that prior knowledge or expectations can lead to errors in interpreting pap smears and spinal images (13)(14)(15)(16)(17).…”
Section: Cognitive Bias: a Preliminary Definitionmentioning
confidence: 99%